Church and state in the Roberts court : Christian conservatism and social change in ten cases, 2005/2018 - Waltman, Jerold L., 1945- (McFarland & Company, Inc., Publishers, 2019)
"This analysis reaches beyond legal doctrines and focuses on four important aspects of change in the American religious landscape: increasing religious diversity; the rise of secularism; the growing political influence of gay and lesbian groups. The author examines how these have influenced how the Supreme Court under Chief Justice John Roberts has dealt with church-state cases"--